2006
DOI: 10.3846/16486897.2006.9636883
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation Into Toxic Impact of Road Maintenance Salt on Grass Vegetation

Abstract: Plants experience a number of stresses in the environment, including those caused by salts, drought, heavy metals and frost. To maintain safety during winter, deicing salt (sodium chloride) is sprinkled over roads. In global practice, natural and laboratory investigations of the impact of road maintenance salts on various species of plants are carried out. So far in Lithuania, only single cases of such investigations have occurred. The aim of this investigation is to determine which of the analysed herbaceous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Investigations of the resistance of grass vegetation to the toxic impact of road salts showed that the most quickly germinating plant (in 1-2 weeks) and the most resistant to the impact of toxins (up to 20 g/kg NaCl in soil) is perennial ryegrass (Lolium perenne L.), while meadow fescue (Festuca pratinsis Huds. L.) or Kentucky bluegrass (Poa pratinsis L.) germinates only in the 5th-6th week of investigation [21].…”
Section: Impact On Vegetationmentioning
confidence: 99%
“…Investigations of the resistance of grass vegetation to the toxic impact of road salts showed that the most quickly germinating plant (in 1-2 weeks) and the most resistant to the impact of toxins (up to 20 g/kg NaCl in soil) is perennial ryegrass (Lolium perenne L.), while meadow fescue (Festuca pratinsis Huds. L.) or Kentucky bluegrass (Poa pratinsis L.) germinates only in the 5th-6th week of investigation [21].…”
Section: Impact On Vegetationmentioning
confidence: 99%
“…Atliekant žolinės augmenijos antžeminės dalies aukščio tyrimus, pastebėta, kad druskos kiekis ištirpusiame sniege turi tiesioginės įtakos pakelės augmenijos antžeminės dalies aukščiui: kuo didesnė NaCl koncentracija, tuo antžeminė dalis žemesnė [1][2][3][4][5][6][7][8][9][10][11].…”
Section: įVadasunclassified
“…In one way or another, if introduced salt into the plants slow down their growth, disrupts other physiological characteristics. Salt affect areas therefore slows photosynthesis and slows water evaporation [2].…”
Section: Introductionmentioning
confidence: 99%